The role of nucleic acid sensors in antifungal immunity - Liang, Xinyu; Zhou, Hui; Ouyang, Litong; Chen, Jiming; He, Wenji (Frontiers in Immunology, 2025)
Fungal infections pose a grave threat to individuals with compromised immune systems, and the accelerated proliferation of drug-resistant strains has led to a marked decline in the effectiveness of conventional antifungal medications in clinical settings. Achieving a more profound comprehension of the mechanisms underlying the host-pathogen interaction is imperative for the effective management of such infections. This review methodically elucidates the pivotal role of nucleic acid sensors as a pivotal subclass of pattern recognition receptors in antifungal immunity, their regulatory networks, and their competitive relationship with pathogen escape strategies. The present study focuses on cytoplasmic and endosomal nucleic acid sensors, delving into their critical roles in antifungal immunity and elucidating three aspects: recognition mechanisms, host regulatory mechanisms, and fungal escape. The results demonstrate that the functions of nucleic acid sensors exhibit significant pathogen specificity, reflecting their personalized and precise roles in antifungal immunity. Furthermore, within the regulatory mechanisms of nucleic acid sensors in the host, the processes of ubiquitin modification and autophagy pathway signaling balance are of significant importance. Concurrently, fungi have been observed to circumvent immune defenses through modifications to their cell walls and the secretion of immunosuppressive factors. This study reveals that the dynamic interplay between the Nucleic acid sensor network and fungal escape strategies holds clinical application potential, providing theoretical support and directional recommendations for clinical immune intervention strategies targeting ubiquitinylation nodes, cell death effector molecules, and other drug-resistant fungi.